Effectiveness and outcome of management strategies for dabigatran- or warfarin-related major bleeding events. Issue 140 (April 2016) - Majeed, Ammar; Hwang, Hun-Gyu; Eikelboom, John W.; Connolly, Stuart; Wallentin, Lars; Feuring, Martin; Brueckmann, Martina; Noack, Herbert; Yusuf, Salim; Schulman, Sam
Abstract: Background: Strategies used for the management of dabigatran-related major bleeding events (MBEs), and their effectiveness have not been systematically evaluated. Methods: Reports on 1034 individuals experiencing 1121 MBEs (696 on dabigatran, and 425 on warfarin) in 5 phase III randomized controlled trials were assessed independently by two investigators. Results: MBEs were managed either by drug discontinuation only (37%), or drug discontinuation with either transfusion of only red cell concentrates (38%), or plasma (23%). Few MBEs (2%) were treated with coagulation factor concentrates. The effectiveness of the management was assessed as good in significantly larger proportion of MBEs on dabigatran (91%) than on warfarin (84%, odds ratio [OR] 1.68; 95% confidence interval [CI], 1.14–2.49), which was consistent with the lower 30-day mortality (OR (OR 0.66; 95% CI, 0.44-1.00)). The effectiveness of bleeding management in non-traumatic bleeding was better in patients with dabigatran than with warfarin (OR 1.82; 95% CI, 1.18–2.79) but was similar in traumatic bleeding (OR 0.75; 95% CI, 0.25–2.30). The relative effectiveness of management of bleeding and 30-day mortality rates across other key subgroups of patients or sites of bleeding, the use of platelet inhibitors, age-, sex- and renal function subgroups, were comparable in MBEs on dabigatran or warfarin. Conclusion: Despite the unavailability of a specific antidote at the time of these studies, bleeding in patients receiving dabigatran was managed in the overwhelming majority of patients without coagulation factor concentrates, with comparable or superior effectiveness and lower 30-day mortality rates versus those who bleed while receiving warfarin. Highlights: Bleeding on dabigatran can mostly be managed without specific hemostatic agents. Overall management effectiveness for dabigatran bleeding is better than warfarin. Bleeding management effectiveness in subgroups is better or comparable to warfarin.